Relationship between geomorphology of the ocean seafloor with the tectonic structure of the Earth's crust and anomalous geophysical fields: Makran Trench, Arabian Sea - Lemenkova, Polina (Geology, Geophysics and Environment, 2020)
This study examined the relationships between topographic structure and submarine geomorphology, sediment thickness, geophysical anomaly fields, geological settings and tectonic lineament stretching of the Arabian Sea region, Carlsberg Ridge morphology, Makran Trench depths by GMT. The study included spatial analysis of the high-resolution datasets (GEBCO, EGM96, GlobSed) and geomorphological modeling of the 300km-width cross-section profiles of the Makran Trench. The analysis shown correlation between complex geologic and tectonic structure, asymmetric geomorphology and geophysical anomaly fields. The Makran Trench is formed in the subduction zone of the Arabian and Eurasian plates at the basement of the continental margin of Pakistan. Submarine geomorphic structure of the Arabian Sea is complicated by the Carlsberg Ridge, Owen Fracture Zone, Aden-Owen- Carlsberg Triple junction, numerous faults and rifts. The geophysical fields of the marine free- air gravity correlate with distribution of these geomorphic structures. Bathymetric analysis of the trench revealed the most frequent depth (448 samples) at -3,250 to -3,500 m, following by intervals: -3,000 to -3,250 m (225 samples), -2,750 to -3,000 m (201 samples). Gently declining continental slope of the coastal elevations correlate with gradually decreasing depths, as equally distributed bins: 124 samples (-2,500 to -2,750 m), 96 (-2,250 to -2,500 m), 86 (-2,000 to -2,250 m). Makran Trench has asymmetric geomorphology with a high slope steepness on the continental slope of Pakistan and low steepness with flat valley on the oceanward side.